Testicular Immune Cells in Murine and Human Fetal Development and Implications for Male Reproductive Health - Hosseini, Samira; Justus Liebig University Giessen (My University, 2022)
A considerable number of studies have investigated human and mouse adult testis immunophysiology, however a fundamental knowledge gap remains in understanding the identity and distribution patterns of immune cells in crucial phases of fetal testis development. This knowledge would facilitate a better understanding of immune cells' contribution to the earliest stages of testis development and lead to knowledge of factors that impact on immune cells to influence testis development. This PhD research project provides knowledge of the frequency, phenotype and distribution pattern of macrophages, T cells, neutrophils (and mast cells), as all are important cell types during fetal testis development in mice, C57BL6J (embryonic ages 13.5 and 15.5 and newborn, in Chapter 2) and in human (2nd and 3rd trimesters, in Chapter 4). Briefly, this study documented for the first time the progressive emergence of neutrophils and T cells, the frequency and localisation of macrophages, T cells, neutrophils and their ratios with germ cells in the developing mice fetal testis. The findings from this study are in alignment with the timing of haematopoiesis in the murine yolk sac, fetal liver and bone marrow. Also, we demonstrated the co-localisation of macrophages and neutrophils with germ cells inside cords (in mice, C57BL6J) and peri cord area (in humans), which can imply the importance of this crosstalk for germ cell differentiation. By revealing the frequent and close cellular contacts between macrophages, T cells and neutrophils during testis development, we provided information that will be key to understanding how immune cells function during the fetal testis development and their influence on the maturation of the earliest male germ cells. The information gained from this study should be considered in developing strategies to support in vitro germline growth, for example, by adding immune cells into scaffolds or organoids. Moreover, the findings of this study revealed similarities and differences in the testicular immune cell population, frequency and locations between mice (C57BL6J) and humans during fetal development. In addition, this thesis provides findings on the impact of activin A levels on mouse fetal testicular macrophages using activin mutant mice (Inhba and Inha) in Chapter Three. The importance of activin A is due to its increased levels during inflammation, infection and pregnancy pathogenesis. Additionally, it is known that activin A levels significantly impact macrophages' function. This part of the thesis demonstrated that activin A levels regulate testicular macrophages frequency, distribution pattern and mRNA 5 levels of involved factors in their pro- and anti-inflammatory functions. The roles of macrophages, mast cells and T cells in testicular cancer have been studied for decades; however, neutrophils as a key pro-inflammatory immune cell have poorly been investigated. In Chapter Five, the study of neutrophils in samples from healthy men and patients with testicular cancers suggests their possible contribution to seminoma pathogenesis. In conclusion, the studies presented in this thesis examined testicular immune cells in fetal and newborn wild type (C57BL6J) and activin mutant mice (Inhba and Inha), human fetal testis, and human adult testicular cancer.
Keywords: Male reproductive immunology; ddc:570; ddc:610